Pendidikan Multikultural di Pondok Pesantren sebagai Solusi Penangkal Faham Radikalisme - Susanti, Salamah Eka (Lembaga Yasin AlSys, 2023)
This research started with the researcher's desire to see how to hide the values of multicultural education found in Islamic boarding schools, where students come from different regions and of course different cultures and ethnicities. They were then united in a boarding school environment and lived in a dormitory which is the hallmark of a boarding school. It is very interesting to note that in Islamic boarding school life there are a series of activities that are carried out both formal activities at school and non-formal in the dormitory and also activities outside the Islamic boarding school. This type of research is library research using descriptive analytical method, namely a method that seeks to systematically present discussion materials originating from various sources to then be analyzed carefully in order to obtain results as conclusions. Data collection methods are through observation, interviews, and documentation. While the approach used by researchers is a sociological-anthropological approach. From the research results, it can be concluded that: 1) Multiculturalism is a meeting point for various cultures that necessitates achievement and appreciation in the midst of cultural plurality. 2) multiculturalism education that is able to create transformative and dialogic nuances towards other cultures. Open yourself up, appreciate, protect, complement and complement each other, not the other way around, namely penetracion pacifigures or presenting violence and egocentricity. 3) Multicultural Islamic boarding schools also support the development of tolerance so that in the pesantren community an inclusive understanding grows for the harmonization of religions in the midst of a plural society that protects the existence of various religious variations.